High Efficiency High Power Density Bidirectional Non-Isolated LLC Converter With Transformer-Coupled Gate Driver for 48 V MHEV - Song Ding; Chunyan Nie; Qi Liu; Qinsong Qian; Weifeng Sun (IEEE Open Journal of Power Electronics)
In this article, a 12-switch non-isolated LLC (NI-LLC) converter is proposed to address the application requirements of 4:1 bidirectional fixed-ratio voltage conversion in 48 V mild hybrid electric vehicles (MHEVs). Compared with the previous NI-LLC converters, the proposed 12-switch NI-LLC converter has superior efficiency and enables inherent bidirectional operation without requiring energy flow direction detection or additional control schemes for forward and reverse modes. Additionally, to synchronously turn on and off power switches in the proposed converter and to reduce gate drive loss and layout area, a transformer-coupled resonant gate driver is proposed. This driver circuit consumes only 18.7% of the power of conventional gate drive circuits, thereby ensuring high efficiency and power density in the converter. Unlike conventional resonant gate driver, the proposed gate driver not only recovers the charge energy, but also significantly reduces the ON/OFF time of main switches. Finally, the proposed converter and gate driver is verified on a 1.2 MHz/960 W prototype with a power density up to 5.6 kW/inch3. The converter achieves a peak efficiency of 98.5%, and the full load efficiency at forward and reverse operation are 97.1% and 96.7% respectively.